PCDD, PCDF, PCB and thiamine in Baltic herring (Clupea harengus L.) and sprat [Sprattus sprattus (L.)] as a background to the M74 syndrome of Baltic salmon (Salmo salar L.) - Vuorinen, Pekka J.; Parmanne, Raimo; Vartiainen, Terttu; Keinänen, Marja; Kiviranta, Hannu; Kotovuori, Olli; Halling, Folke (ICES Journal of Marine Science, 2002)
Baltic herring and sprat were sampled between October 1994 and January 1995 off the southern coast of Finland and around the Åland Islands. From this material fish of 135–159 mm in length, a size class that was assumed to be preferred as prey by Baltic salmon, were selected and grouped according to species, sex and age. Herring were 1–3 years and sprat 3–13 years old. In addition, one group of smaller, two-year-old, female sprat was selected. Thus twenty groups were formed and prepared as whole-fish homogenates. Thiamine was quantified from all homogenates, while female and male sprat and female herring were analysed for polychlorinated biphenyls (PCBs), dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs). There were no significant differences between sexes within each species in the total thiamine concentrations, but the mean total thiamine concentration in 1 to 3-year-old herring (8.6 nmol g−1) was higher than that in 2 to 13-year-old sprat (6.7 nmol g−1). The mean-fresh-weight concentrations of total PCBs, coplanar PCBs, PCDDs and PCDFs were on average 2–3 times higher in 2 to 10-year-old sprat than in 1 to 3-year-old herring of a similar size, although the difference in PCDD concentrations was not significant. In sprat females there were no significant correlations between age or fat content and the fresh-weight concentrations of coplanar PCBs or PCDFs. However, the higher OC concentrations in sprat could be explained both by their higher fat content, with the younger age groups being the most fatty, and by their age, which reflects their slower growth rate. The fat-weight-based total PCB, PCDD, PCDF and coplanar PCB concentrations increased with age in sprat and, after controlling for age, there was a significant positive relationship between the fat content and the fresh-weight-based concentrations of OCs, apart from total PCBs. On a fat-weight basis the concentration of coplanar PCBs was also higher in sprat than in herring. It is concluded that the Baltic salmon is provided with an adequate supply of ...